Clinical decision support system impact on diagnostic imaging appropriateness and value-driven outcomes in a Singapore emergency department: Protocol of a pragmatic controlled before-after study - Yi Xiang Tay; Shane J. Foley; Ronan Killeen; Jeremy C.P. Wee; Ivan S.Y. Chua; Marcus E.H. Ong; Peter Doran; Robert Chun Chen; Lai Peng Chan; May San Mak; Jonathan P. McNulty (PLoS ONE, 2025)
Modern medicine relies heavily on diagnostic imaging because of its beneficial role in the healthcare chain. Imaging rates are increasing globally and are expected to continue to rise in the future. In tandem with this phenomenon is the increase in inappropriate imaging that adversely affects the provision of healthcare and increases the risks to patients. To date, effective interventions to reduce inappropriate imaging have shown conflicting results due to various underlying implementation designs and strategies. The aim of this controlled before-after study is to assess the impact of a clinical decision support system (CDSS) on appropriateness rates of X-ray cervical and lumbar spine in the emergency department (ED) compared to the existing practice without one, while also exploring associated outcomes. In this study, a CDSS will be carried out using implementation science principles to enhance evidence uptake with institutional medical board-approved imaging referral guidelines embedded. Recruited ED physicians will be allocated into control and intervention groups. The control group will continue the routine practice of “do nothing” for four months, while the intervention group will have a two-month CDSS intervention after an initial two-month routine practice of “do nothing”. The difference between the baseline and post-implementation appropriateness rate of imaging will be compared. This study will also evaluate the impact of CDSS on clinical effectiveness, cost avoidance, radiation doses, and sustainability. Findings from this before-after study will provide a rigorous, pragmatic test of the impact and effect of radiological CDSS as an evidence-based intervention to reduce inappropriate imaging in the ED.